DEVELOPING INQUIRY LEARNING MODEL-BASED ELT MATERIALS FOR THE SEVENTH GRADE OF JUNIOR HIGH SCHOOL - Ariana Mappe Amir; Djuwairiah Ahmad; Sitti Nurpahmi (ELTIES : English Language Teaching for EFL Learners, 2019)
This research is aimed at developing English materials for students of the seventh grade especially in basic competencies 3.7 & 4.7 and 3.8 & 4.8 at MTs Madani Pao-pao based on 2013 curriculum supported by using inquiry learning model and using HOTS characteristic in indicators achieved. The research design used in this study was Research and Development (R&D). The development model used was ADDIE model. It consists of needs analysis, design, development, implementation, and evaluation. The procedures included analyzing materials needed by spreading questionnaire to the students and analyzing the basic competencies used, designing a blueprint of materials which include indicators, HOTS characteristic and inquiry learning model, developing the English materials through ADDIE model. Types of data obtained in this study are quantitative and qualitative data. The instruments used in this research were the syllabus including basic competency, questionnaire, table of basic competency analysis, a blueprint of material design and validation checklist for expert. Therefore, the result indicated that based on experts’ judgment as well as product development result, the developed basic competency 3.7& 4.7 and basic competency 3.8 & 4.8 were applicable to be taught at the seventh grade students of Junior High School as topics in English for them.